2015
DOI: 10.3324/haematol.2015.130112
|View full text |Cite
|
Sign up to set email alerts
|

Genomic patterns associated with hypoplastic compared to hyperplastic myelodysplastic syndromes

Abstract: While the bone marrow in most patients with myelodysplastic syndromes (MDS) has normal or increased cellularity (hyper-MDS), approximately 10%-15% of MDS patients will present with a hypocellular bone marrow (hypo-MDS).1 Since the diagnosis of MDS relies mainly on the presence of dyplastic morphology of myeloid precursors and/or the presence of recurrent chromosomal abnormalities, low cellularity aspirates in patients with hypo-MDS may compromise morphologic evaluation and karyotypic analyses, and ultimately c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 14 publications
2
22
0
1
Order By: Relevance
“…These cases have differences in genetic profiles that include a lower rate of mutations and a lower frequency of splicing factor gene mutations compared with hyperplastic patients. 68 This pattern is more similar to that observed in SAA. is difficult to evaluate when considering hMDS vs SAA or nonsevere AA.…”
Section: Introductionsupporting
confidence: 84%
“…These cases have differences in genetic profiles that include a lower rate of mutations and a lower frequency of splicing factor gene mutations compared with hyperplastic patients. 68 This pattern is more similar to that observed in SAA. is difficult to evaluate when considering hMDS vs SAA or nonsevere AA.…”
Section: Introductionsupporting
confidence: 84%
“…[28][29][30][31] So far, few genetic studies have focused on h-MDS, without firm conclusion. [32][33][34][35] In a recent study on patients with unexplained cytopenia, including MDS and AA, we found that mutation profiling has a high predictive value for identifying individuals with a myeloid neoplasm. [36] In particular, selected mutation patterns were proven highly specific for myeloid neoplasms with myelodysplasia, which may possibly identify bona fide MDS even in the absence of definitive morphological features, as previously acknowledged for selected cytogenetic abnormalities.…”
Section: Introductionmentioning
confidence: 85%
“…Gene mutations have started to be taken into account for risk stratification of myeloid malignancies recently, and cumulating data are suggesting that certain gene mutations have prognostic significance in MDS [ 22 , 23 ]. Of particular interest, Nazha et al recently reported the genomic analysis of 237 MDS patients, in which h-MDS patients comprised 14% [ 10 ]. In their study, there was no difference in the distribution of cytogenetic abnormalities between their NH-MDS and h-MDS subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, age-adjusted criteria of marrow hypocellularity have also been proposed to define h-MDS, for instance, <30% cellularity in patients younger than 70 years and <20% cellularity in patients older than 70 years, to account for the physiologically deceasing marrow cellularity with increasing age [ 6 8 ]. Although h-MDS share a number of similar clinical features with NH-MDS, and both have a propensity to leukemic transformation during clinical follow-up, h-MDS appear to be a distinct clinico-pathological entity [ 9 , 10 ], suggesting an unique underlying pathogenesis of this disease. Recently, a number of somatic mutations, such as mutations in ASXL1, EZH2, TET2, IDH1/2, DMNT3A, RUNX1, NRAS, KRAS, TP53 , and splicing complex genes, which may play important roles in the pathogenesis of MDS, have been described [ 11 ].…”
Section: Introductionmentioning
confidence: 99%